Replacement Procedure and Mechanism Lost Minuta Deed Due Natural Disaster - Chaerullah Wahyu; Amin Purnawan (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2020)
The purpose of this study as follows: 1) to identify and explain the procedures and mechanisms replacement of Lost Minuta Due due to natural disasters that occurred in Palu, Central Celebes. 2) to identify and explain the barriers and solution procedures and mechanisms replacement of Lost Minuta Due due to natural disasters that occurred in Palu, Central Celebes. The method used in this research is descriptive using normative juridical approach. Sources of data obtained by collecting primary data and secondary data. Primary data were collected by interview and secondary data obtained through primary legal materials, secondary law and tertiary legal materials. Based on the results of this research to know that the procedures and mechanisms Replacement of Lost Minuta Due Natural Disaster is Making a report that the notary with Lost Minuta Deed to the police, but if the minutes of the deed is lost due to force majeure or break up the core of the minutes of the deed can not be read again the notary shall make an official report which will then be submitted to the news event MPW or MPD. 1) make a report to the police to report content that the notary concerned has lost all documents and other important files. 2) send the report to the Minister of Justice and Human Rights of the Republic of Indonesia concerning the condition of the notary's office damaged by natural disasters. 3) send a letter containing a report to the Director of the Department of Civil Law and Human Rights of the Republic of Indonesia, Directorate General of Legal Administration, Solution: 1) heirs to apply for approval of the minutes of the notary deed or protocol to the notary who willing to accept the minutes of a notary deed or protocol of the notary who had died or disappeared because of natural disasters. 2) notary willing to accept the minutes of a notary deed or protocol to apply to the Minister of Justice and Human Rights of the Supervisory Council cq region of Central Celebes province of Indonesia concerning the appointment of the protocol. 3) after a petition submitted and accepted by the Supervisory Council of the Territory, then the Regional Supervisory Council issued a decree on appointment of notaries container protocol of notary who died or disappeared because of natural disasters.